Implementación de un sistema inteligente de orientación vocacional para determinar el tipo de ocupación utilizando la lógica difusa - Ramos Sigcha, Israel Lenin (2023)
This research arises from the need for support in the field of vocational guidance for students who are about to start their university stage or dedicate themselves to a trade after finishing their high school studies. In order to allow them to choose a university career or professional training according to their personality, the proposal of a fuzzy logic based intelligent system is presented, which aims to serve as support for an expert in the field of vocational guidance. This document shows the process of modeling, development and implementation of the intelligent system following the Prometheus methodology and using the Prometheus Design Tools for the modeling process. Subsequently, the identification of requirements, conceptualization, formalization of structures, implementation of rules and the application of tests are detailed with the help of the phases established by the Buchanan methodology. To determine the ideal type of occupation for a person, the intelligent system is based on the analysis of several aspects of personality, for which the already established structure of the Holland Vocational Orientation Test, proposed by John Lewis Holland, is taken as reference. Finally, the reliability of the system is verified by a contrast between the results of the physical test and the intelligent system, where the effectiveness can be noted when determining the ideal type of occupation for students. Additionally, a 95% reliability is obtained for use as support for decision-making by a specialist professional in the area of vocational guidance.